PENGARUH PENYULUHAN MATERI HIV/AIDS TERHADAP PENGETAHUAN DAN SIKAP REMAJA DI SMA DARMA BHAKTI MEDAN TAHUN 2018 - darwita juniwati (Universitas Prima Indonesia, 2018)
HIV/AIDS is one of the health problems that should receive more attention worldwide because it has become a problem of people from various countries including Indonesia. The age group of adolescents are highly vulnerable to HIV / AIDS because of their knowledge is lacking and their attitude is not positive. One intervention that has been done is to provide counseling. The purpose of this study was to determine the effect of education about HIV / AIDS materials on the knowledge and attitudes of the students of class X- XI of the Public High School Darma Bhakti Medan. This study is a Quasi-experimental trial using the design of one group pre-post test. The population of this research is all class X-XI students consisting of 59 subjects and samples are taken using total sampling technique and 59 individuals was obtained as a sample. Wilcoxon test was used in data analysis. As a result of the study, P-value = 0.000 or p <0.05 was obtained for the knowledge and values of P = 0.000 or p <0.05 for attitude. As the conclusion is that counseling about HIV / AIDS materials are influencing knowledge and attitudes . As the conclusion is that counseling about HIV / AIDS materials are influencing knowledge of the students of class X –XI of the Public High School Darma Bhakti Medan. The students are encouraged to actively seek the latest information on HIV / AIDS, among others, by reading the latest sources to obtain correct and comprehensive understanding.